Teachers' Perception of Principal's Leadership Style and The Implication on Teachers' Professionalism - Gazali, Nadien Irfatin Nuha; Bafadal, Ibrahim (Proceedings Series of Educational Studies, 2025)
This study aims to analyze teachers' perceptions of principals' leadership styles and the implications for teacher professionalism using the Systematic Literature Review (SLR) method. Through the collection and analysis of relevant literature, this study identifies various leadership styles applied by principals, including authoritarian, democratic, and transformational styles, and their impact on teacher motivation and performance. The results of the analysis show that teachers' positive perceptions of principals' leadership styles contribute significantly to their improved professionalism. Inclusive and participatory leadership styles proved effective in creating a supportive work environment, increasing commitment, and promoting the development of teachers' pedagogical competencies. This study concludes that principals need to apply adaptive leadership approaches to improve the quality of education in schools. The implications of the findings emphasize the importance of leadership training for principals to strengthen the relationship between leadership and teacher professionalism